Legal Protection For Notaries In Carrying Out Their Duties As Public Officials - Desy Artha Pertiwi (Faculty of Law Universitas Muhammadiyah Metro, 2026)
The principle of the rule of law is to guarantee certainty, order, and legal protection based on truth and justice. Article 1868 of the Civil Code is the basis for the authority of notaries in drawing up authentic deeds. In practice, there are legal issues related to notarial deeds. The main issues of this study are: 1) How is legal protection regulated for notaries in carrying out their duties as public officials; 2) How Notaries Perform Their Duties and Responsibilities as Public Officials. Protection for notaries in carrying out their duties is very necessary. Legal protection for notaries in carrying out their duties takes the form of fulfilling the rights of notaries as officials and as individuals, in accordance with the provisions of the 1945 Constitution. Preventive legal protection is provided through supervision and guidance by the Notary Supervisory Council, the Notary Law and its implementing regulations, and the Notary Code of Ethics. Repressive legal protection (resolution) is provided in the form of sanctions imposed on notaries who are proven guilty of violating their duties. Legal protection for the notary profession through the Notary Honorary Council (MKN) can be carried out repressively because it is related to the application of Article 66 paragraph 1 of the Notary Profession Law, namely in granting approval or rejecting requests from investigators who wish to summon notaries in court proceedings.